2012
DOI: 10.1371/journal.pgen.1002953
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transposon-Derived Small RNAs in the Interplay between Genomes and Parasitic DNA in Rice

Abstract: RNA silencing is a defense system against “genomic parasites” such as transposable elements (TE), which are potentially harmful to host genomes. In plants, transcripts from TEs induce production of double-stranded RNAs (dsRNAs) and are processed into small RNAs (small interfering RNAs, siRNAs) that suppress TEs by RNA–directed DNA methylation. Thus, the majority of TEs are epigenetically silenced. On the other hand, most of the eukaryotic genome is composed of TEs and their remnants, suggesting that TEs have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 32 publications
(37 reference statements)
1
72
0
Order By: Relevance
“…Surprisingly, no expression was detected in W1514 despite the presence of more than 18 copies of MIR820. 7 Accordingly, no cleavage of OsDRM2 by miR820 was detected in W1514 (Fig. 1B).…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Surprisingly, no expression was detected in W1514 despite the presence of more than 18 copies of MIR820. 7 Accordingly, no cleavage of OsDRM2 by miR820 was detected in W1514 (Fig. 1B).…”
mentioning
confidence: 91%
“…1C). 7 The qRT-PCR revealed that the absence of miR820 in W1514 is due to a reduced level of the pre-miR820 transcript, rather than to its reduced processing. This implies that the high copy number of MIR820 in wild rice accession with BB or BBCC genome may cause a stronger MIR820 silencing in these species.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…It is likely that, during RdDM, double-stranded RNAs (dsRNAs) are processed to produce ~21-24 nt small interfering RNA (siRNAs), which direct de-novo methylation of original genomic locations and trigger epigenetic silencing (Aufsatz et al, 2002). Profi ling of small RNAs in the plant genomes has demonstrated that LTR-RTs are one of the major sources to generate small RNAs (Lu et al, 2005;Nosaka et al, 2012). As illustrated in Fig.…”
Section: Review Protein Cellmentioning
confidence: 99%